Victim #8 - Abramson, Traci Hunter (A Luke Steele Novel, 2025)
"Haunted by a failed mission, military aide Luke Steele teams up with FBI Special Agent Amberlyn Reiner to investigate a journalist's suspicious death in Istanbul. They uncover a conspiracy threatening millions of US citizens, including the president, with nuclear destruction. Amid the danger, Luke must overcome self-doubt and trust in his budding relationship with Amberlyn as they work to stop the catastrophic plot in time"--